Formulation and Characterization Of Benzoyl Peroxide Loaded Stearic Acid Based Nanoparticles For Enhanced Stability - Madhwani, Chirag; Chauhan, Pradeep (Journal of Neonatal Surgery, 2025)
The objective of the current investigation was to develop stearic acid nanoparticles loaded with benzoyl peroxide to improve the stability of BPO as well as to control the release of the same from the formulation for a longer duration. The nanoparticles were prepared by solvent evaporation/emulsification method using stearic acid and lecithin as lipid component and tween 80 as the surfactant. The blank nanoparticles were found to be 191.4 nm whereas the average particle size of the formulations ranged from 211.7 to 451.2 nm. The zeta potential of the formulations was high and ranged between -19.1 mV to -21.6 mV. The entrapment efficiency ranged from 59.4 to 83.7%. The optimized formulation exhibited particles size of 211.7 nm with polydipsersity index (PDI) of 0.313 and zeta potential of -21.6 mV. The optimzied formulation (SNP4) was subjected to stability study of vesicles at different temperatures. It was observed that only about 1.43% degradation occurred at room temperature and all formulations were almost stable at 8° and 40° with only 1.4% degradation of BPO thereby proving the stability of the developed system.